2011
DOI: 10.1108/01437731111112999
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in action: student leadership development in an event management course

Abstract: The purpose of this paper was to examine the leadership practice scores and leadership behaviors of students before and after an event management course. A mixed methods approach was utilized. The StudentLeadership Practice Inventory (S-LPI) was administered to a sample of 184 students in three semesters of an event management course. Students completed the S-LPI at the beginning and at the end of the course. The students also wrote reflections of their leadership behaviors and learnings.Results of the study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…As a result of a study conducted by Külekçi (2016), it was found that education was effective in the development of students' leadership skills in leading a group. In a similar study conducted by Marcketti et al (2011) in relation to development of student leadership in the event management course, it was found that the students' mean scores increased significantly for all the application areas between before and after. Özçelik-Herdem (2019) suggests in a study that efforts should be made to start developing self-leadership skills of the students.…”
Section: Discussionmentioning
confidence: 82%
“…As a result of a study conducted by Külekçi (2016), it was found that education was effective in the development of students' leadership skills in leading a group. In a similar study conducted by Marcketti et al (2011) in relation to development of student leadership in the event management course, it was found that the students' mean scores increased significantly for all the application areas between before and after. Özçelik-Herdem (2019) suggests in a study that efforts should be made to start developing self-leadership skills of the students.…”
Section: Discussionmentioning
confidence: 82%
“…Influenced by their teachers and the activities carried out in class, individuals strengthen their leadership qualities. In their study, [25] stated that on the subject of students' leadership development, the positive relationships formed with their friends and outside class made a positive contribution to students' development. On the other hand, it is stated that in terms of the student's psychological and academic needs, being in communication with the school principal and teacher is important from the viewpoint of organising the student's own lifestyle and increasing his/her competences [1,37].…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…This event is intended so that students have a responsible leadership spirit and can organize or manage the organization. Arent et al [20] suggested that leadership practice scores and student leadership behaviors increased after managing events/events. In addition to managing this school event, students are also trained in entrepreneurship, because when they hold an event they must be able to find funds to fulfill the event.…”
Section: Background Of Egalitarian Culture In Yogyakarta State Seniormentioning
confidence: 99%